Synthesis and characteristics of novel TPA-containing electrochromic poly(ether sulfone)s with dimethylamino substituents. (1st February 2021) - Huang, Chiao-Ling; Kung, Yu-Ruei; Shao, Yu-Jen; Liou, Guey-Sheng
Abstract: Newly designed dimethylamine-substituted triphenylamine (TPA) derivatives, N, N' -(1, 4-phenylene)bis( N -(4-(( tert -butyldimethylsilyl)oxy)phenyl)- N'', N'' -dimethylbenzene-1, 4-diamine) (NTPPA-2Si ) and N, N '-((1, 1′-biphenyl)-4, 4′-diyl)bis( N -(4-(( tert -butyldimethylsilyl)oxy)phenyl)- N'', N'' -dimethylbenzene-1, 4-diamine) (NTPB-2Si ), with silyl ether protecting groups were readily synthesized. Subsequently, novel electroactive aromatic poly(ether sulfone)s (PES), NTPPA-PES and NTPB-PES, could be obtained from silyl polycondensation. The PESs were readily soluble in commonly used laboratory organic solvents and could be solution-cast into tough and amorphous films with moderate levels of glass-transition temperature around 220°C and thermal stability without significant weight loss up to 400 °C under nitrogen or air atmosphere. The Nernst equation method was used to explore the number of electrons transferred at each oxidation step of the targeted two monomers. Furthermore, these two anodic electrochromic PESs were introduced into electrochromic devices accompanied with cathodic heptyl viologen (HV), and the resulted devices demonstrated a high coloration contrast and excellent electrochemical stability.